A Diverse Social and Emotional Learning Booklist for Gifted Learners and Advanced Readers. Issue 1 (2nd January 2023) - Garces-Bacsal, Rhoda Myra; Alhosani, Najwa Mohammed; Elhoweris, Hala; Tupas, Ruanni
ABSTRACT: Despite the changing school demographics indicating an increasingly greater diversity in today's classrooms, research indicates how teachers have little cognizance of the cultural backgrounds of their students. This becomes an issue among gifted students who are double minorities: those who are gifted and of a different cultural background, or of low-income status, rendering them doubly vulnerable. One of the ways this can be addressed is by introducing diverse books with an international focus to 9- to 12-year-old gifted students allowing them to see themselves reflected in what they read and to facilitate the learning of social and emotional learning competencies. Using the critical multicultural analysis framework and strategies on promoting multicultural awareness, recommended activities and discussion questions are provided to educators.